Flowmetry/pelvic floor electromyographic findings in patients with detrusor overactivity - Alizadeh, Farshid (Int Braz J Urol, 2015)
To evaluate different flowmetry/EMG patterns in patients with proven detrusor overactivity (DO) and compare them with that of a group of patients with lower urinary tract symptoms (LUTS) but without DO. MATERIALS AND METHODS: We retrospectively evaluated the records of 100 patients with frequent urinary tract infection or any kind of storage or voiding symptoms that had undergone urodynamic testing: 50 cases with proven DO on cystometry who had a good quality flowmetry/EMG and 50 patients without DO. EMG lag time (the time distance between pelvic floor EMG inactivation and the start of urine flow) and different flow curve pattern were recorded and compared. RESULTS: The age and gender distribution were not statistically significant between the two groups. A negative lag time (≤ 0 sec) and an obstructive pattern were the only parameters that were more commonly seen in the DO group. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of a lag times <2 sec for diagnosing DO were 70%, 96%, 96% and 72%, respectively. For a negative lag time, they were 52%, 100%, 100% and 63%, respectively. CONCLUSIONS: A lag time < 2 sec is a useful flowmetric finding that effectively rules out patients with LUTS that do not have DO (specificity and PPV=96%). With the cutoff of zero or less, specificity and PPV will be 100%. It has lower sensitivity and NPV, however, and is not measurable in a considerable population of patients with DO that have concomitant DV.